The economics of agrobiodiversity conservation for food security under climate change - Pascual, U.; Narloch, U.; Nordhagen, S.; Drucker, Adam G. (2011)
Subsistence-based and natural resource-dependent societies are especially vulnerable to climate change. In such contexts, food security needs to be strengthened by investing in the adaptability of food systems. This paper looks into the role of agrobiodiversity conservation for food security in the face of climate change. It identifies agrobiodiversity as a key public good that delivers necessary services for human wellbeing. We argue that the public values provided by agrobiodiversity conservation need to be demonstrated and captured. We offer an economic perspective of this challenge and highlight ways of capturing at least a subset of the public values of agrobiodiversity to help adapt to and reduce the vulnerability of subsistence based economies to climate change.